Development potentials of foreign direct investments: Comparative international experiences - Antevski Miroslav (Međunarodni Problemi, 2009)
In this paper the author analyses the main development potentials of foreign direct investments in different world regions. They are real and evident, but not always exploited. It is found out that the developed financial markets, good governance, developed institutions and the size of country have a great impact on the location choices of foreign investors. In developing countries economic, administrative and legislative reforms, as well as developed infrastructure networks, should improve a country's attractiveness for FDIs. In most countries, FDIs are concentrated in developed regions and sell the greatest share of their production on the local market. One of their parts is export-oriented, but at the same time, they are great importers from developed countries. The extent of spillovers is modest in most cases.